Understanding the mediating effects of technology factor on social media acceptance among budget accommodations - Noraihan Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2022)
The characteristics of social media and its interactivity propelled it to become an eminent medium of marketing for most business organisations, including SMEs. However, SMEs in the hospitality and tourism industry, such as budget accommodations, hardly utilise social media as their marketing medium. Thus, this study investigates factors influencing budget accommodation owners in utilising social media as their marketing medium since digital promotion remains underexplored in SMEs. The current study adopts an expanded research model consisting of the Technology Acceptance Model (TAM) and Innovation Diffusion Theory (IDT), where 300 respondents were selected and assessed using the convenience sampling technique. An analysis of Partial Least Square-Structural Equation Modelling (PLS-SEM) was employed to test the research model. Research analysis revealed that the exogenous constructs refer to the internal factor, while external and technology factors jointly explained 71.6% variance of the endogenous construct of social media acceptance. External and technological factors positively and significantly affect social media marketing acceptance among budget accommodation. However, internal factors show insignificant effects. The analysis of mediating effects illustrated that technological factors greatly mediate both internal and external factors on social media marketing acceptance among budget accommodation. In conclusion, the findings of this study provide useful insights into the perspectives of budget accommodation owners in social media marketing, which indirectly contributes to the development of the nation’s tourism industry and economic growth.